SEMINAR DAN SKRINING NYERI LUTUT DI RSUD LAPATARAI KABUPATEN BARRU (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2025)
Knee pain is a significant health issue that affects the quality of life of the adult population in Indonesia. Identifying the causes of knee pain requires comprehensive information, including age, clinical history, symptom onset, pain location, and supporting diagnostic examinations. A holistic and integrated approach to managing knee pain is essential to reduce its negative impact. Therefore, education for healthcare professionals and the general public is crucial, particularly through seminars and early detection via screening. This activity aimed to provide education and early detection for patients at Lapatarai Regional Public Hospital regarding knee pain. The event was conducted in collaboration with the Orthopedic Department of the Faculty of Medicine, Hasanuddin University, over two days. It consisted of seminars using presentation methods and knee pain screening, attended by patients at Lapatarai Hospital. A total of 37 participants took part in the event, comprising 20 individuals with knee pain and 17 without. The seminar's effectiveness was evaluated through pre- and post-tests, which demonstrated a significant improvement in participant scores. The number of participants scoring ≥7 increased significantly (p-value < 0.05), indicating enhanced knowledge following the seminar. Screening results showed that most participants experiencing knee pain had no history of trauma. This condition is likely associated with unhealthy lifestyles, such as being overweight and having weak knee-supporting muscles. Additionally, the use of methylprednisolone and unidentified herbal medications were also found to be potential contributing factors.   ---   Nyeri lutut merupakan kondisi kesehatan yang signifikan mempengaruhi kualitas hidup masyarakat dewasa di Indonesia. Untuk mengetahui penyebab nyeri lutut, diperlukan informasi seperti usia, riwayat klinis, onset gejala, lokasi nyeri, dan pemeriksaan penunjang lainnya. Pendekatan yang komprehensif dan terpadu dalam penanganan nyeri lutut sangat diperlukan untuk mengurangi dampak negatifnya. Oleh karena itu, diperlukan edukasi pada tenaga kesehatan serta masyarakat mengenai hal tersebut, salah satunya adalah dengan seminar dan deteksi dini dengan skrining. Tujuan dari kegiatan ini adalah untuk memberikan edukasi dan deteksi dini pasien di RSUD Lapatarai mengenai nyeri lutut. Kegiatan dilaksanakan bersama dengan tim Orthopedi dari Fakultas Kedokteran Universitas Hasanuddin selama 2 hari, yang terdiri dari kegiatan seminar dengan metode presentasi, dan kegiatan skrining nyeri lutut yang dihadiri oleh pasien-pasien di RSUD Lapatarai. Terdapat 37 peserta yang hadir pada acara, dengan 20 peserta menderita nyeri lutut dan 17 peserta tidak nyeri lutut. Keberhasilan seminar dinilai berdasarkan hasil pre-test yang lebih baik dibandingkan dengan hasil post-test. Hasil pre dan post test didapatkan peningkatan signifikan jumlah peserta dengan skor ≥7 dengan hasil p-value < 0.05 yang berarti terdapat peningkatan pengetahuan pada peserta. Berdasarkan hasil skrining, mayoritas pasien yang mengeluhkan nyeri lutut tidak memiliki riwayat trauma. Hal ini kemungkinan disebabkan oleh gaya hidup yang kurang sehat, seperti kelebihan berat badan dan otot yang lemah di sekitar lutut. Selain itu, penggunaan obat methylprednisolone dan obat-obatan herbal yang tidak jelas juga ditemukan menjadi faktor potensial.
Keywords: Knee pain; Seminars; Counseling; Screening; Early detection